DESAIN DIDAKTIS SISTEM PERSAMAAN LINEAR TIGA VARIABEL DI KELAS X MA AL-MUSTAQIM - Sumiatik, Sumiatik; Mirza, Ade; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research generally aims to clarify and solve learning obstacle in the problem solving of System of Linear Equations In Three Variables in the tenth grade of MA Al-Mustaqim Kubu Raya. To minimize the learning obstacles, the didactic design was arranged. The form of this research was didactic design research with a qualitative approach. This study was conducted by giving the pre-test questions of problem solving to 27 students, then selecting four students to be the research subjects randomly. After analyzing the results of the pre-test, students experienced learning obstacles in understanding the problem, arranged a solution plan, implementing a settlement plan, and recheck the results obtained. After that, the researcher arranged the didactic design in the form of learning scenarios and the student worksheets. The didactic design that has been prepared is tested on research subjects. After that, the researcher gave the post-test questions. The post-test results showed that the obstacles that experienced by the four research subject reduced Â Keywords: Didactical Design, Learning obstacles, Problem Solving